(untitled) (International relations and international law Journal, 2021)
The research article would be devoted to the study on the new EU-Central Asia strategy for partnership, which has been presented this year in Bishkek, Kyrgyzstan. Given geopolitical characteristics of region countries and importance of Central Asian region for the world leading countries and economies, authors develops further research ideas on the theoretical, methodological and legal basics of that strategy. For almost three decades of partnership, Central Asia has become of a great strategic importance to the European Union due to the geographic location of the region between Asia and Europe and mutual common interests in cooperation issues. The new EU-CA cooperation strategy lies within the general foreign policy of the European Union towards its neighboring countries and regions. The author tries to find and justify changes and challenges of new strategy, comparing to the previous one, and comes to the conclusion on the inevitable importance of the European Union for the future development of Central Asian region. Key words: European Union, Central Asia, new strategy, partnership, aspects.